1997
DOI: 10.1055/s-2007-972647
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Body Composition in Competitive Swimmers by Means of Three Different Techniques

Abstract: Up to now controversial reports have been published in regard to the beneficial effects of swimming, a non-weight-bearing activity, on bone mass (BM). Therefore, the aim of this study was to investigate the effects of competitive swimming practice on the bone mineral density (BMD) and bone mineral content (BMC) as well as on the different factors of body composition. For this purpose, competitive swimmers (16 males and 16 females) were selected as subjects in order to investigate the influence of swimming on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 1 publication
1
18
0
6
Order By: Relevance
“…Although the findings were not significant in the current study, males increased in body mass (D ¼ 0.9 kg, P ¼ .15), which appeared to be largely attributable to an increase in LM (D ¼ 0.8 kg, P ¼ .23). Previous investigators 12,15 reported that 13 However, Avlonitou et al 16 reported BMD values (as measured by DEXA) of female and male competitive swimmers that were similar to those of age-matched controls. Our DEXA measures of BMD also indicated that both male and female swimmers were in the healthy range for total body BMD Z scores compared with age-matched controls (females ¼ À0.12 6 0.8, males ¼À0.26 6 1.3).…”
Section: Discussionmentioning
confidence: 88%
“…Although the findings were not significant in the current study, males increased in body mass (D ¼ 0.9 kg, P ¼ .15), which appeared to be largely attributable to an increase in LM (D ¼ 0.8 kg, P ¼ .23). Previous investigators 12,15 reported that 13 However, Avlonitou et al 16 reported BMD values (as measured by DEXA) of female and male competitive swimmers that were similar to those of age-matched controls. Our DEXA measures of BMD also indicated that both male and female swimmers were in the healthy range for total body BMD Z scores compared with age-matched controls (females ¼ À0.12 6 0.8, males ¼À0.26 6 1.3).…”
Section: Discussionmentioning
confidence: 88%
“…Our results are in agreement with results of previous studies. Soccer [4], basketball [5,6], volleyball [5][6][7], gymnastics [4,6], weightlifting [8] and ice hockey [9] are associated with a high TB BMD, whereas cyclists [10], horse riders [11] and especially swimmers [5,9,10,[12][13][14][15] have a TB BMD similar to that of a sedentary group. These results emphasize the effect of gravity on bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exercise, both impact loading such as running and of nonimpact exercise such as cycling and swimming appears to clearly favor impact‐loading exercise in both young men and women. This advantage appears to hold through early adulthood as measured in elite competitive athletes [151,159‐165]. There does seem to be a slight difference between men and women during these later competitive years, with men building slightly more bone than women [150,151,159,165,166].…”
Section: Applications In Geriatric and Osteoporosis Rehabilitationmentioning
confidence: 99%
“…This advantage appears to hold through early adulthood as measured in elite competitive athletes [151,159‐165]. There does seem to be a slight difference between men and women during these later competitive years, with men building slightly more bone than women [150,151,159,165,166]. Even in later years, the athletes have greater bone mineral content than nonathletic controls, which demonstrates the value of early‐life athletic activity, especially for women who are at greater risk for osteoporosis.…”
Section: Applications In Geriatric and Osteoporosis Rehabilitationmentioning
confidence: 99%